O processo de implementação do SUAS: um estudo sobre o trabalho desenvolvido pelo CRAS no noroeste paulista - Guimarães, Elaine Friozi Garcia [UNESP] (2015)
This research has as object of study the process of SUAS implementation from the work developed by the CRAS, in the everyday reality of DRADS coverage of region Fernandópolis. Aims to analyze the process of SUAS implementation in the Northwest of São Paulo on CRAS quest for completion of the social assistance while social right. We use the qualitative approach, the prospect of working with the meanings of social reality from the experiences of the subjects of this research. In order to achieve the materialization of this proposed study, we carried out bibliographical research, desk research and field research, which was developed in the municipalities of CRAS Macaubal, Populina, Riolândia and Rubinéia. In the field research we use the techniques of the questionnaire and focus group. It is visible social assistance, historically conceived as charity and bounty, from the 1988 Federal Constitution went on to occupy a new place now within social policies, through its legal recognition as social right. We present the progress achieved through the creation of the LOAS (1993), the PNAS (2004) and the institution of SUAS (2005), however, we highlight the challenges faced everyday so that this right will be effective throughout the country, especially when we consider the socio-economic context in which we operate, marked by neoliberalism, that arises against constitutional advances and the possibilities of assistance assurance as a social right. In this context, we seek to learn about the prospect of SUAS workers about the work developed by the CRAS, discussing the possibilities and challenges of every day and also on the main strategies used in the deployment/implementation of the SUAS, within the perspective of the search for effectiveness of the right to social assistance